Morphological evolution, growth mechanism, and magneto-transport properties of silver telluride one-dimensional nanostructures - Li, GaoMin (Springer, 2013)
Single crystalline one-dimensional (1D) nanostructures of silver telluride (Ag(2)Te) with well-controlled shapes and sizes were synthesized via the hydrothermal reduction of sodium tellurite (Na(2)TeO(3)) in a mixed solution. The morphological evolution of various 1D nanostructures was mainly determined by properly controlling the nucleation and growth process of Ag(2)Te in different reaction times. Based on the transmission electron microscopy and scanning electron microscopy studies, the formation mechanism for these 1D nanostructures was rationally interpreted. In addition, the current–voltage (I-V) characteristics as a function of magnetic field of the highly single crystal Ag(2)Te nanowires were systematically measured. From the investigation of I-V characteristics, we have observed a rapid change of the current in low magnetic field, which can be used as the magnetic field sensor. The magneto-resistance behavior of the Ag(2)Te nanowires with monoclinic structure was also investigated. Comparing to the bulk and thin film materials, we found that there is generally a larger change in R (T) as the sample size is reduced, which indicates that the size of the sample has a certain impact on magneto-transport properties. Simultaneously, some possible reasons resulting in the observed large positive magneto-resistance behavior are discussed.